Membangun Personality dan Potensi Guru TK Melalui Self Development Di Kecamatan Sawangan Kotamadya Depok - Wartiningsih, Endah; Mariam, Iis; Latianingsih, Nining; Purwinarti, Titik; Sofa, Nidia (Unit Penelitian dan Pengabdian kepada Masyarakat (UP2M) Politeknik Negeri Jakarta, 2019)
In the current era of globalization and information technology, the world of education is challenged to always be adaptive to changes that occur in the surrounding environment and have an impact on the patterns of teaching and services carried out by stakeholders such as at the level of basic education, namely kindergarten (kindergarten). The pattern of education and teaching will not succeed without being equipped with a pattern of service from administrative staff, teachers and school principals to students, parents of students, fellow students and to the community. Friendly service is a service that refers to the pattern of administrative services which is pima. To produce excellent service quality, it requires a training for kindergarten teachers in the field of office administration through self-potential development. In this dedication there are two kindergarten partners in Sawangan-Depok sub-district involved, namely: TK Islam Perkasa and TK Aisyiah Bustanul Afthal 17. The problem that arises is the self-potential and personality development of the kindergarten teacher in the service and learning process must still be improved. Therefore, in this service, it is expected that there will be a transfer of knowledge and experience (transfer of knowledge and experience) in teaching patterns, ways of exploring one's potential and improving strong personal qualities through self development so that the quality of learning becomes superior. The resulting output is a model of self-introduction, self-potential, grooming for educators that can be published in national journals.